Investigation on characteristic behaviour on developing atomizer for fine spray using PIV - Asmuin, Norzelawati; Khalid, Amir; Mohideen Batcha, Mohd Faizal (Penerbit UTHM, 2020)
One of the major factor to pollution today is the use of hydrofluorocarbon (HFCS) in the domestic household aerosols. Globally, there are around 20 billion devices manufactured annually and the UK has F4 most share of this market manufacturing 5 billion units which are second only to the USA. Therefore, it is desirable that hydrofluorocarbons should be replaced with the non-Volatile Organic Compound (non-VOC) in order to reduce the impact on the environment. This project aims to generate the fundamental data and understanding required to produce fine sprays whilst using the limited to the energy available from pressurizing liquid at a few bar pressures using a non-flashing propellant gas. A major challenge in this research is minimizing droplet size, such as volume median drop diameter D and D to less than 70 microns and to ensure that the entire content of the can is emptied.